HLA ligandomics identifies histone deacetylase 1 as target for ovarian cancer immunotherapy. (3rd May 2016) - Peper, Janet Kerstin; Bösmüller, Hans-Christian; Schuster, Heiko; Gückel, Brigitte; Hörzer, Helen; Roehle, Kevin; Schäfer, Richard; Wagner, Philipp; Rammensee, Hans-Georg; Stevanović, Stefan; Fend, Falko; Staebler, Annette
Abstract: The recent approval of clincially effective immune checkpoint inhibitors illustrates the potential of cancer immunotherapy. A challenging task remains the identification of specific targets guiding immunotherapy. Facilitated by technical advances, the direct identification of physiologically relevant targets is enabled by analyzing the HLA ligandome of cancer cells. Since recent publications demonstrate the immunogenicity of ovarian cancer (OvCa), immunotherapies, including peptide-based cancer vaccines, represent a promising treatment approach. To identify vaccine peptides, we employed a combined strategy of HLA ligandomics in high-grade serous OvCa samples and immunogenicity analysis. Only few proteins were naturally presented as HLA ligands on all samples analyzed, including histone deacetylase (HDAC) 1 and 2. In vitro priming of CD8 + T cells demonstrated that two HDAC1/2-derived HLA ligands can induce T-cell responses, capable of killing HLA-matched tumor cells. High HDAC1 expression shown by immunohistochemistry in 136 high-grade serous OvCa patients associated with significantly reduced overall survival (OS), whereas patients with high numbers of CD3 + tumor-infiltrating lymphocytes (TILs) in the tumor epithelium and CD8 + TILs in the tumor stroma showed improved OS. However, correlating HDAC1 expression with TILs, high levels of TILs abrogated the impact of HDAC1 on OS. This study strengthens the role of HDAC1/2 as an important tumor antigen in OvCa, demonstrating its impact on OS in a large cohort of OvCa patients. We further identified two immunogenic HDAC1-derived peptides, which frequently induce multi-functional T-cell responses in many donors, suitable for future multi-peptide vaccine trials in OvCa patients.